1997
DOI: 10.1148/radiology.205.1.9314973
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery stenosis: detection and quantification with spiral CT angiography versus optimized digital subtraction angiography.

Abstract: Spiral CT angiography enabled accurate assessment of renal artery stenosis in patients with possible renovascular hypertension and may assist in selecting patients for interventional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(39 citation statements)
references
References 0 publications
0
38
0
1
Order By: Relevance
“…This was a rather exploratory study designed to evaluate a spinal cord compression model and compare two imaging techniques. Reports suggest agreement between CT angiography and digital subtraction angiography are very high (r > 90%) for evaluation of vascular components (Link et al 1996, Kaatee et al 1997. Despite the relative small study population, DSV and CT venography consistently demonstrated changes in IVVP morphology during experimental spinal cord compression.…”
Section: Digital Subtraction Venographymentioning
confidence: 91%
“…This was a rather exploratory study designed to evaluate a spinal cord compression model and compare two imaging techniques. Reports suggest agreement between CT angiography and digital subtraction angiography are very high (r > 90%) for evaluation of vascular components (Link et al 1996, Kaatee et al 1997. Despite the relative small study population, DSV and CT venography consistently demonstrated changes in IVVP morphology during experimental spinal cord compression.…”
Section: Digital Subtraction Venographymentioning
confidence: 91%
“…[5][6][7][8] The diagnostic role of conventional angiography continues to diminish as noninvasive CT and MR angiography develop. [4,6,8] Parameters that favor noninvasive vascular imaging include patient's comfort, duration of the examination, reduced complication rate [9,10] and diminished cost. However, conventional angiography still has superior resolution for the evaluation of small vessels and offers the option of simultaneous therapeutic interventions such as percutaneous revascularization by balloon angioplasty and/or stenting.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Magnetic resonance (MR) angiography (MRA) and computed tomography angiography are oriented toward depicting anatomy rather than tissue injury. 7,8 Radionuclide captopril renography has not been widely accepted 9 because of its limited accuracy in the presence of bilateral disease 10 or therapy with ACE inhibitors. 11 Inhibiting the activity of the AT 1 R with angiotensin receptor blockers or ACE inhibitors, on the other hand, is widely adapted by clinicians to protect the kidney from renal injury.…”
mentioning
confidence: 99%